2021
DOI: 10.3390/nu13020372
|View full text |Cite
|
Sign up to set email alerts
|

Green Salad Intake Is Associated with Improved Oral Cancer Survival and Lower Soluble CD44 Levels

Abstract: Deficiencies in fruit and vegetable intake have been associated with oral cancer (oral cavity and oropharyngeal). Salivary rinses contain measurable biomarkers including soluble CD44 (solCD44) and total protein, which are known markers of oral cancer risk. This study investigates the effect of nutritional factors on solCD44 and protein levels to evaluate oral cancer risk and survival. We evaluated solCD44 and protein levels from 150 patients with oral and oropharyngeal squamous cell carcinoma and 150 frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…No statistically significant difference was found between participants with no/1–5 teeth removed at baseline versus at 12 months (48.9% vs. 45.5%, p = 0.180). There was no statistically significant difference between the proportions of participants with no/mild alcohol consumption at baseline versus at 12 months according to previously published criteria [ 23 ] for alcohol consumption (18.2% vs. 15.9%, p = 0.625). We recently found an inverse association between CD44 levels and green salad/vegetable intake [ 23 ].…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…No statistically significant difference was found between participants with no/1–5 teeth removed at baseline versus at 12 months (48.9% vs. 45.5%, p = 0.180). There was no statistically significant difference between the proportions of participants with no/mild alcohol consumption at baseline versus at 12 months according to previously published criteria [ 23 ] for alcohol consumption (18.2% vs. 15.9%, p = 0.625). We recently found an inverse association between CD44 levels and green salad/vegetable intake [ 23 ].…”
Section: Resultsmentioning
confidence: 60%
“…There was no statistically significant difference between the proportions of participants with no/mild alcohol consumption at baseline versus at 12 months according to previously published criteria [ 23 ] for alcohol consumption (18.2% vs. 15.9%, p = 0.625). We recently found an inverse association between CD44 levels and green salad/vegetable intake [ 23 ]. Here, no statistically significant difference was found between baseline and 12-month values for the proportions of participants consuming less than one or zero salads per week (39.8% vs. 38.6%, p = 0.705), consumption of other vegetables less than once per week (5.7% vs. 6.8%, p = 1.000), consuming green salad or other vegetables less than once per week or never (2.3% vs. 4.5%, p = 0.500), and consuming green salad and other vegetables less once per week or never (66.7% vs. 33.3%, p = 0.508).…”
Section: Resultsmentioning
confidence: 60%
“…Smoking, alcohol consumption, poor dental hygiene, the human papillomavirus, and betel nut consumption are most commonly reported risk factors of oral cancer ( 6 12 ). However, in addition to the conventional risk factors described above, other environmental factors including dietary and nutrients have also been reported in recent research ( 13 15 ). The significance of vegetables and fruits abundant in dietary fiber and vitamins in carcinogenesis is garnering more attention among dietary factors ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 87%
“…Some vegetables, e.g., lettuce, broccoli, cabbage, onion, and garlic, can effectively protect against cancer of the mouth, throat, esophagus, and stomach [55]. The studies by Bradford-Bella et al have shown that eating vegetables and green salad at least once a week reduces the concentration of an oral cancer marker (CD44) in saliva and improves the prognosis of oncological patients [56]. These reports are consistent with the results of this study, indicating the protective role of vegetable consumption in the development of oral cancer.…”
Section: Fruit and Vegetable Consumption And The Risk Of Oral Cancermentioning
confidence: 99%